Nuclear-Reaction Control by Multistage Mathematical-Programming - I. Leikkonen; K. Haugset (Modeling, Identification and Control, 1980)
The method of Multistage Mathematical Programming (MMP) has been adapted for optimal control of the spatial power distribution in nuclear reactors. Changes in power distribution arise from variations in the operational conditions of the reactor, and excite oscillations which in large reactors may approach the stability limit.